FRI0137 UPADACITINIB IMPROVES PATIENT-REPORTED OUTCOMES IN PATIENTS WITH RHEUMATOID ARTHRITIS AND INADEQUATE RESPONSE TO METHOTREXATE: RESULTS FROM SELECT-COMPARE. (June 2019) - Strand, Vibeke; Bergman, Martin; Tundia, Namita; Ostor, Andrew; Durez, Patrick; Song, In-Ho; Enejosa, Jose Jeffrey; Schlacher, Casey; Song, Yan; Fleischmann, Roy
Abstract : Background: Upadacitinib (UPA), a selective JAK1 inhibitor, has demonstrated superior improvement in the clinical signs and symptoms of rheumatoid arthritis (RA) compared with placebo (PBO) and adalimumab (ADA). 1 Objectives: To evaluate the effect of UPA vs PBO and vs ADA on patient-reported outcomes (PROs) at Week 12 in SELECT-COMPARE (NCT02629159 ), a randomised controlled trial (RCT) in an active RA population with inadequate responses to methotrexate (MTX). Methods: Patients in SELECT-COMPARE, a phase 3 RCT, received UPA (15 mg once daily), PBO, or ADA (40 mg every other week) while on background MTX therapy. The following PROs were collected prospectively: Patient Global Assessment of Disease Activity (PtGA) by visual analogue scale (VAS), pain by VAS, Health Assessment Questionnaire Disability Index (HAQ-DI), duration and severity of morning (AM) stiffness, health-related quality of life by Short Form-36 (SF-36), Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F), and Work Instability Scale for RA (RA-WIS). Least squares mean (LSM) changes from baseline (BL) to Week 12 were based on mixed-effects repeated measures models. The proportions of patients reporting improvements ≥ minimum clinically important differences (MCID) from BL to Week 12 or scores ≥ normative values were determined with UPA, PBO, and ADA treatment; comparisons used chi-square tests. Results: Data from 1629 patients (UPA: 651; PBO: 651; ADA: 327) were analysed. Mean age was 54 years; 79% were female; 54% had RA for ≥5 years. Baseline mean PRO scores were similar across treatment groups. At Week 12, UPA treatment resulted in statistically significant LSM changes from BL vs PBO across all PROs and statistically significant LSM changes from BL vs ADA in PtGA, pain, HAQ-DI, AM stiffness severity, FACIT-F, and SF-36 physical component summary (PCS) and 6/8 domain scores (Table ). ADA treatment resulted in statistically significant LSM changes from baseline vs PBO in PtGA, pain, HAQ-DI, AM stiffness severity and duration, FACIT-F, and SF-36 PCS and 5/8 domain scores. Compared with PBO at Week 12, significantly more UPA-treated patients reported improvements ≥ MCID and scores ≥ normative values across all PROs with numbers needed to treat (NNTs) <10. The proportions of UPA-treated patients reporting improvements ≥ MCID were similar or numerically higher than ADA-treated patients. Importantly, the proportion of UPA vs ADA treated patients reporting improvements ≥ normative values were significantly greater (all p <0.05) in PtGA (36% vs 26%), HAQ-DI (21% vs 14%), SF-36 PCS (16% vs 11%), and SF-36 bodily pain (29% vs 21%) and vitality (42% vs 35%) domains. Conclusion: Among patients with active RA, treatment with UPA 15 mg QD on background MTX therapy for 12 weeks resulted in statistically significant and clinically meaningful improvements in PROs compared with PBO. Overall, PRO improvements with UPA treatment met or were superior to treatment with ADA, especially in key domains of pain, function and vitality. References: [1] Fleischmann R, et al. Arthritis Rheumatol. 2018;70(S9), abstract 890. Acknowledgement: AbbVie sponsored the study and contributed to the design, analysis and interpretation of data. Medical writing services were provided by Brandy Menges of JK Associates Inc. and were funded by AbbVie. Disclosure of Interests: Vibeke Strand Consultant for: AbbVie, Amgen, Bayer, BMS, Boehringer Ingelheim, Celgene, Celltrion, CORRONA, Crescendo, EMD Serono, Genentech/Roche, GSK, Horizon, Inmedix, Janssen, Kezar, Lilly, Merck, Novartis, Pfizer, Regeneron, Samsung, Sandoz, Sanofi, Servier, UCB., Martin Bergman Shareholder of: Johnson and Johnson (parent company of Janssen), Consultant for: AbbVie, Amgen, BMS, Celgene, Genentech/Roche, Janssen, Merck, Novartis, Pfizer, and Sanofi/Regeneron, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Genentech/Roche, Janssen, Merck, Novartis, Pfizer, and Sanofi/Regeneron, Namita Tundia Shareholder of: AbbVie, Employee of: AbbVie, Andrew Ostor Consultant for: AbbVie, BMS, Roche, Janssen, Lilly, Novartis, Pfizer, UCB, Gilead, Paradigm, Patrick Durez Speakers bureau: BMS, Lilly, Sanofi, and Celltrion, In-Ho Song Shareholder of: AbbVie Inc, Employee of: AbbVie Inc, Jose Jeffrey Enejosa Shareholder of: AbbVie Inc, Employee of: AbbVie Inc, Casey Schlacher Shareholder of: AbbVie, Employee of: AbbVie, Yan Song Employee of: Analysis Group Inc., which received consulting fees from AbbVie for this study, Roy Fleischmann Grant/research support from: AbbVie, Amgen, AstraZeneca, Bristol-Myers Squibb, Celtrion, Genentech, GSK, Janssen, Lilly, Novartis, Pfizer Inc, Sanofi-Aventis, UCB, Consultant for: AbbVie, Amgen, AstraZeneca, Bristol-Myers Squibb, Celtrion, Genentech, GSK, Janssen, Lilly, Novartis, Pfizer Inc, Sanofi-Aventis, UCB